1987
DOI: 10.1139/v87-403
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects in cooxidation: Cr(VI) – oxalic acid – sulfoxides systems

Abstract: The kinetics of cooxidation of several substituted phenyl methyl sulfoxides and oxalic acid with Cr(V1) have been carried out in the presence of perchloric acid. The reaction is first order each in sulfoxide, oxalic acid, Cr(VI), and H'. The products of oxidation are sulfones and carbon dioxide. Electron-releasing groups in the phenyl ring accelerate the rate while electron-withdrawing groups retard it. The Hammett correlation yields a reaction constant of -0.927 +-0.08 ( r = 0.994) at 313 K. Addition of alumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
3
5
0
Order By: Relevance
“…Substituent effect studies can give an insight into the mechanism of [(salen)Mn v O] + oxidation of organic sulfoxides. The observed ρ-value of −2.57 ± 0.09 is close to the ρ-values found for the oxidation of substituted phenyl methyl sulfoxides by potassium bromate [32] (ρ = −2.05) and by chloramine-T [33] (ρ = −2.02). These reactions were characterized as proceeding through an electrophilic attack by a halogen ion on the sulfur centre of the sulfoxide in the rate-determining step.…”
Section: Mechanism Of the Oxygen Atom Transfer From Oxomanganese(v) Tsupporting
confidence: 80%
See 2 more Smart Citations
“…Substituent effect studies can give an insight into the mechanism of [(salen)Mn v O] + oxidation of organic sulfoxides. The observed ρ-value of −2.57 ± 0.09 is close to the ρ-values found for the oxidation of substituted phenyl methyl sulfoxides by potassium bromate [32] (ρ = −2.05) and by chloramine-T [33] (ρ = −2.02). These reactions were characterized as proceeding through an electrophilic attack by a halogen ion on the sulfur centre of the sulfoxide in the rate-determining step.…”
Section: Mechanism Of the Oxygen Atom Transfer From Oxomanganese(v) Tsupporting
confidence: 80%
“…: (i) a rate-determining electrophilic attack of the oxidant on the sulfur of the sulfoxide [10,[32][33][34][35][36]; (ii) a single electron transfer from the sulfoxide to the metal ion in the rate-limiting step [37][38][39]; and (iii) a nucleophilic attack of the oxidant on the sulfoxide in the ratedetermining step [3,40,41], have been reported so far for the oxygenation of organic sulfoxides. In the present investigation, let us consider how the oxygen atom is actually transferred from the oxo species to the sulfoxide in the rate-limiting step.…”
Section: Mechanism Of the Oxygen Atom Transfer From Oxomanganese(v) Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Such complex formation between the oxidant and oxalic acid is indispensable for co-oxidation to occur [17]. In the present case too, addition of oxalic acid to Cr(VI) leads to a substantial hyperchromic shift at 263 nm and 351 nm in the UV-vis spectra of Cr(VI) (Figure 4(b)) which indicates the involvement of Cr(VI) in complex formation.…”
Section: Mechanismsupporting
confidence: 51%
“…Srinivasan et al [17] reported the co-oxidation of phenylmethyl sulfoxides and oxalic acid with Cr(VI) and designed the mechanism for the reaction which also highlights the substituent effect. Das et al [18] monitored the micellar effect on the cooxidation of dimethyl sulfoxide and oxalic acid by Cr(VI) considering it as a probe for three-electron transfer in a single step.…”
Section: Introductionmentioning
confidence: 99%